Morphologic evaluation of the pre-lacrimal recess using computed tomography - Cunha-Cabral, Diogo (2024)
Objetives: This work aims to evaluate the morphology of the pre-lacrimal recess (PLR) of the maxillary sinus (MS) in the Portuguese population. Material e Methods: We performed a retrospective analysis of computed tomography images of the paranasal sinuses of 75 patients (150 sides). Multiple morphologic parameters of the MS and of the PLR were evaluated, such as the pneumatization of the MS, the width of the PLR, the thickness of the medial wall of the PLR and the angle of the piriform notch (APN). We also studied the relationship between the anterior superior alveolar nerve (ASAN) and the medial wall of the PLR. Results: None of the analyzed hypoplasic MS (6/250) had PLR. PLR was present in 86,2% and 88,0% of the normal and hyperplasic MS, respectively. The average width of the PLR was 4,90 +/- 1,69 mm. Its medial wall had an average thickness of 3,14 +/- 1,86 mm. There was an inverse association between the width of the PLR and the thickness of its medial wall (p<0,001). There was also an association between the degree of pneumatization of the MS and the thickness of the medial wall of the PLR. In hyperplasic MS this wall was significantly thinner (p=0,009). The APN had a mean amplitude of 43,94 +/- 12,14º. The ASAN was in a vulnerable position in almost 40% of the cases. Conclusion: The high variability of the anatomy of the PLR implies that a detailed morphologic evaluation of this region using CT scan in order to correctly select the patients that can benefit from a pre-lacrimal endoscopic approach.